Feedback Focused: A Learner- and Teacher-Centered Curriculum to Improve the Feedback Exchange in the Obstetrics and Gynecology Clerkship - Natasha R. Johnson; Andrea Pelletier; Celeste Royce; Ilona Goldfarb; Tara Singh; Treven C. Lau; Deborah D. Bartz (Association of American Medical Colleges, 2021)
Introduction Learners consistently report insufficient feedback, despite interventions to improve the quantity and quality of feedback. Effective feedback requires a dynamic partnership and a trusting relationship between students and teachers. Methods We developed and implemented a faculty and student program called Feedback Focused on the OB/GYN clerkship with learner- and faculty-centered teaching materials. We evaluated the curriculum's impact on the frequency and quality of feedback exchange through comparison of end-of-clerkship evaluations before and after implementing the Feedback Focused program and assessed student satisfaction from written responses on clerkship evaluations. Results A total of 1,912 feedback folio entries were recorded during the curriculum timeframe, representing an average of 19 entries per student. Of students, 85% turned in their feedback folios at the end of the clerkship. There was a marked increase in reported frequency of feedback with the initiative, with 28% of students reporting receiving feedback four or more times per month before the start of our program, compared to 64% after its completion. The percentage of students who reported faculty provided direction and constructive feedback always or very often remained roughly the same before and after the program (69% vs. 70%, respectively). Over 60% of students provided positive feedback on written open response questions. Discussion We successfully developed and implemented a multipronged approach to effectively change the learning environment culture within our OB/GYN clerkship program. Our evaluation demonstrated that the Feedback Focused program was well received and increased frequency of feedback.